EFFECT OF FAMILY CHILDREN MODIFIED MODEL ON FAMILY EMPOWERMENT IN MALANG ELEMENTARY SCHOOL - Apriyani Puji Hastuti; Hanim Mufarokhah Mufarokhah (Jurnal Kesehatan Hesti Wira Sakti, 2018)
Background: Malnutrition and over nutrition in school-age children is a serious problem because it will continue into adulthood which is a risk factor for various metabolic and degenerative diseases such as cardiovascular disease, diabetes mellitus, cancer, osteoporosis, etc. In children with malnutrition and over nutrition can also cause a variety of health problems that interfere with the quality of life such as disorders of leg growth, sleep disturbances, stop breathing for a moment and other respiratory disorders. The high number of malnutrition and over nutrition in Indonesia needs to get easy and affordable treatment by quality health services, one of which is through family empowerment called family empowerment. The family is the first and closest person that affects the child's lifestyle. Healthy lifestyles and not determined by parenting from family or family including diet, eating behavior and children's activities. The application of a balanced lifestyle to school children is not an easy thing. This requires support from various parties, namely parents, family, teachers, health workers and other parties. Objective: The purpose of this study was to determine the effect of modified model family empowerment on the level of family empowerment. Methods: This study was a semi-experiment one group pre and post test design with 172 respondents were taken by purposive sampling technique. Family Empowerment was measured by using Family Empowerment Scale (FES) before and after family empowerment modified model. Family empowerment model was performed at one time and evaluate in 2 month to the family. Analysis of the data was analyzed using Wilcoxon Signed Rank test. Result The level of family empowerment of the control group before intervention was mostly 73 people (85%) and a good small portion was 13 people (15%) with a mean ± SD of 89.54 ± 5.91. The level of family empowerment in the treatment group in the pre-majority was 73 people (85%) and a small portion less than 3 people (3%) with a mean ± SD of 89.02 ± 5.65. After the intervention became quite large as many as 70 people (81%) and a small portion was enough as many as 16 people (19%) with a mean ± SD of 90.17 ± 5.28. The results showed that the Family Empowerment Modified model can increase the level of family empowerment ((Z= 4,226 dan α=0,000) Conclusion: According to the results of this research and because of knowledge increasing and understanding’s family about diet model. Family is the first and closest person that affects the child's lifestyle, it would be balance in nutrition fulfillment of children.